Assessment of cardiovascular risk in patients with androgenetic alopecia using high-sensitivity C-reactive protein and lipoprotein a - Magdy A Ragab; Eman M Hassan; Eman T El Sayed; Salwa A Abdaljawad (Wolters Kluwer Medknow Publications, 2019)
Background The association between androgenetic alopecia (AGA) and cardiovascular risk is still controversial. Objective To evaluate the association between AGA and the risk of cardiovascular diseases (CVDs) using lipoprotein a [Lp (a)] and high-sensitivity C-reactive protein (hs-CRP) as biomarkers of cardiovascular risk. Patients and methods A case-control study was done on 30 patients with AGA and 25 healthy controls with normal hair status. Both patients and their controls were examined generally and locally. Classification of AGA was done according to Hamilton-Norwood scale for male patients and Ludwig's classification for women. Hair examination was confirmed using dermoscopy for the assessment of signs of AGA. All participants were investigated for serum lipids including cholesterol, triglycerides, low-density lipoprotein, high-density lipoprotein, and Lp (a), in addition to hs-CRP. Results After exclusion of the well-known risk factors for CVD, AGA patients showed higher positive family history of CVD in first-degree relatives than the controls. Serum lipids including serum Lp (a) and hs-CRP were significantly higher in AGA patients. Lp (a) was positively correlated with hs-CRP in AGA patients. Both Lp (a) and hs-CRP were positively correlated with the severity of AGA in both men and women. Both markers did not correlate significantly with lipid parameters including cholesterol, triglycerides, low-density lipoprotein, and high-density lipoprotein. There was no significant difference between men and women with AGA as regards the studied parameters. Both hs-CRP and Lp (a) showed significant discrimination using area under the receiver operating characteristic curve where Lp (a) showed area under the curve=0.928 with 95% confidence interval, 0.863-0.993 and P=0.001 while hs-CRP showed area under the curve=0.963 with 95% confidence interval 0.921-1.0, and P value less than 0.001. Multivariate logistic regression analysis showed that hs-CRP was the only significant independent factor affecting cardiac risk in AGA cases. Conclusion AGA patients showed higher risk for CVD. Both Lp (a) and hs-CRP can be used as a predictor for cardiovascular risk in such patients; however, hs-CRP is still considered an independent risk factor for cardiovascular insults in AGA patients.